2010
DOI: 10.1538/expanim.59.479
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Examination of Cyclooxygenase-2 and Renin in a KK-Ay Mouse Model of Diabetic Nephropathy

Abstract: Abstract:The renin-angiotensin system plays a central role in the pathological mechanisms of diabetic nephropathy and is regulated by renal expression of cyclooxygenase-2 (COX-2). In the present study, the kidneys of diabetic KK-A y mice, a model of human type 2 diabetes, were investigated histologically and immunohistochemically at 8, 12, 16, and 20 weeks of age, and changes in renal lesions and expression of COX-2 and renin were evaluated quantitatively. Glomerular damage, characterized by expansion of mesan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Glomerular effects of COX-2 are supported by the fact that macula densa COX-2 expression peaks at a time earlier than glomerular COX-2[58]. Hyperglycemia augments COX-2 mediated-hyperfiltration but lessens the ability of COX-2 to increase GFR in hyperfiltering patients [56] and might signify increased compromise of the glomerular barrier (in addition to vasodilation) mediated by COX-2.…”
Section: Diabetic Nephropathy: More Than Cox-2 Dysregulation Of Hemodmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerular effects of COX-2 are supported by the fact that macula densa COX-2 expression peaks at a time earlier than glomerular COX-2[58]. Hyperglycemia augments COX-2 mediated-hyperfiltration but lessens the ability of COX-2 to increase GFR in hyperfiltering patients [56] and might signify increased compromise of the glomerular barrier (in addition to vasodilation) mediated by COX-2.…”
Section: Diabetic Nephropathy: More Than Cox-2 Dysregulation Of Hemodmentioning
confidence: 99%
“…In female diabetic patients, Ang II-mediated reductions in GFR were abolished by COX-2 inhibition [60]. Glomerular COX-2 expression is correlated with glomerular sclerosis to a higher degree than renin-positivity[58]. Studies also show association between RAS activity and COX-2 expression.…”
Section: Diabetic Nephropathy: More Than Cox-2 Dysregulation Of Hemodmentioning
confidence: 99%
“…17 Furthermore, in most mouse strains, diabetes induces relatively minor glomerular pathology. 18 In this regard, our preliminary studies indicated that in wild-type B6/D2 mice, the strain used to generate the transgenic animals, low-dose streptozotocin-induced (STZ-induced) diabetes did not induce significant diabetic nephropathy, and renal COX-2-positive cells were rare under both basal and diabetic conditions.…”
Section: Podocyte Cox-2 Expression In Diabetesmentioning
confidence: 99%
“…This mouse serves as a model of obese insulin‐resistant T2DM showing hyperglycemia, hypertriglyceridemia and hyperinsulinemia. This experimental model has been used to investigate diabetic nephropathy (Yabuki et al ., ) and has been recently applied in pharmacological studies for the improvement of cognitive decline by angiotensin II type 1 receptor blocker in the brain (Min et al ., ).…”
Section: Introductionmentioning
confidence: 99%